Successful colonoscopic-guided balloon dilation of post-anastomotic stricture in infant: a preliminary report from tertiary care hospital Karachi-Pakistan - Dur-e-Shahwar; Dilawar, Bakhtawar; Sadiq, Kamran; Islam , Saleem (Journal of the Pakistan Medical Association, 2025)
Post-anastomotic strictures, particularly those arising from surgical interventions like right hemicolectomy for necrotising enterocolitis (NEC), present a prevalent and challenging issue in the paediatric setting. This report presents an intriguing case of a neonate admitted to the Neonatal Intensive Care Unit (NICU) with a post-anastomotic stricture following NEC surgery. It provides a comprehensive clinical profile, including radiological, systemic findings, and a detailed outline of the management approach. The patient underwent a successful colonoscopic-guided balloon dilation procedure, achieving a dilation of up to 12 mm. However, recurrent strictures occurred even after a successful dilation of up to 12 mm, which lead to the decision for resecting the stricture and revising the anastomosis. The outcomes demonstrated significant improvement, highlighting the efficacy and potential of this approach. This case report offers valuable insights into the effectiveness of innovative intervention, providing essential information for paediatric healthcare practitioners. Keywords: Post-anastomotic strictures, necrotising enterocolitis, colonoscopic-guided balloon dilation.